Nasal Soft-Tissue Triangle Deformities - Foda, Hossam M.T. (Facial Plastic Surgery, 2016)
The soft-tissue triangle is one of the least areas attended to in rhinoplasty. Any postoperative retraction, notching, or asymmetries of soft triangles can seriously affect the rhinoplasty outcome. A good understanding of the risk factors predisposing to soft triangle deformities is necessary to prevent such problems. The commonest risk factors in our study were the wide vertical domal angle between the lateral and intermediate crura, and the increased length of intermediate crus. Two types of soft triangle grafts were described to prevent and treat soft triangle deformities. The used soft triangle grafts resulted in an excellent long-term aesthetic and functional improvement.
Keywords: rhinoplasty; soft triangle deformities; revision surgery; soft triangle graft